The Accelerated Learning Cycle Model (9E) And Its Impact On Mathematics Achievement Among Second-Year Intermediate Students (Journal of the College of Basic Education, 2025)
The current research aims to identify the effect of the accelerated learning cycle model ((9 E) on the achievement of mathematics among second-grade middle school students. In order to verify the research objective, the null hypothesis was established, which states: "There is no statistically significant difference at a significance level of (0.05) between the average scores of the students of the experimental group that were studied according to the learning cycle model (9 E) and the scores of the control group that were studied in the traditional way in the achievement test", The experimental research method and quasi-experimental design were adopted for two equivalent groups with a post-test. The experiment was applied to the basic research sample, which numbered (68) students, with (37) students for the experimental group and (31) students for the control group for the academic year 2023-2024, They were rewarded in (previous mathematical information, previous achievement in mathematics, intelligence), and the research tool represented by a test was built with the achievement test.Its validity and reliability were verified. The experimental group was taught according to the learning cycle model (9 E) and the control group The control group according to the traditional method, the results showed that the students of the experimental group outperformed the students of the control group in the achievement test, and the research concluded with a set of conclusions, recommendations and suggestions established in the text of the research.